Exploring the potential for local end-processing of e-waste in South Africa - Sadan, Zaynab (Department of Chemical Engineering, 2020)
E-waste is one of the fastest-growing waste streams in the world, and South Africa (SA) is no exception. This is driven by increased consumer demand and access to electrical and electronic equipment, in addition to perceived equipment obsolescence, and rapid advancements in technology. E-waste recycling presents an opportunity in providing a source of secondary resources such as metals, plastics and glass, as well as employment and economic opportunities in both developed and developing countries. Furthermore, the diversion of this waste stream from landfills or dumps prevents additional land use and the potential negative impacts on human health and the environment. E-waste collection and upgrading is a relatively small-scale but growing industry in SA. Only 12% of e-waste generated was estimated to be recycled in 2015. Most of SA’s ewaste volumes are inaccessible due to lack of formal take-back schemes, lack of consumer awareness, as well as e-waste being kept in storage or disposed of in landfills. E-waste recyclers in SA generally carry out collection, dismantling and sorting, refurbishing, as well as pre-processing of value fractions. There is currently limited local end-processing capacity, therefore partially upgraded value fractions are prepared for export, while non-viable fractions are stockpiled or disposed of in local landfills. The business case for local end-processing of e-waste value fractions, particularly metals, does not seem feasible due to the inconsistent and insufficient volumes available. Furthermore, SA faces unique socio-economic challenges such as an unregulated yet well-established informal sector. Additionally, the legal framework presents many inhibitors for e-waste recyclers. This research study builds upon the knowledge that there is a limited understanding of the feasibility of existing e-waste end-processing technologies for implementation in the South African socio-economic and legislative context. Therefore, this research intends to find out what are the key barriers and enablers to implementing e-waste end-processing technologies in SA. Qualitative research methods were used to uncover the current challenges faced by local recyclers and other stakeholders in the value chain. The data collection thus took the form of interviews, site visits and desktop research. The findings show that the e-waste recycling industry in SA is undergoing many new developments in terms of research and investment interest, as well as the anticipated outcomes from the recent submissions of Industry Waste Management Plans (IndWMP). The industry shows potential as an emerging secondary resource economy, however, the extent to which it will mature is dependent on the organisation of its collection network as well as the development of local end-processing and manufacturing capacity. The collection network and infrastructure are currently supported by both informal and formal recyclers who provide a diversity of collection strategies and a wide network of ewaste sources. However, efforts to increase recycling rates by accessing volumes in storage and increasing consumer awareness and engagement is necessary. Besides the economies of scale required to support the development of local end-processing, alternative technologies to large-scale smelting should be considered for the SA context. While this is seen through initiatives by SA Precious Metals, end-processing technologies is still inaccessible to small and medium recyclers due to cash flow issues as well as cherry-picking of high-grade materials. Therefore, recyclers require further support in terms of dealing with non-viable fractions. This includes research and investments into technologies and business models for the recycling of low-value materials including plastics, as well as subsidies for the cost of safe disposal or treatment of these fractions. Additionally, acquisition of product markets and an increase in manufacturing capacity is necessary to accelerate industry development. The legislative framework also poses limitations on recyclers in the e-waste value chain, stemming from the legal definition of e-waste as a liability as opposed to a resource. While the legislation is unlikely to change, provisions to relieve any legal barriers should be implemented. This includes permissions for pilot projects to test new technologies, as well as legal support for smaller recyclers in the form of consultancy as well as guidelines for sustainable waste management practices should be provided. Finally, while there are many challenges present in the e-waste recycling industry today, the IndWMP offers an opportunity for collaboration between key stakeholders, including the relevant government bodies. Plans have been submitted and the outcomes of approved plans will be revealed at the beginning of 2019. The plans offer solutions for recycling subsidies, increasing the collection and recycling rates, as well as investment into technology, research and enterprise development. However, successful implementation of these plans will only occur if integration and collaboration of the local e-waste community prevail over greed and the struggle for power.